Perceptions of risks to elite secondary school education in South Africa - Butler-Wheelhouse, D (2018)
This study engages with the most important risks facing quality education in elite secondary schools in South Africa. It adopts a critical realist perspective that emphasises the importance of perceptions, as they shape the decisions and actions of those faced with risks. Through the use of surveys and in-depth semi-structured interviews, perceptions of a wide range of risks were explored: ranging from classrooms, to schools and their social contexts, to national and global political and economic factors. The perceptions of risks of different participants in this research varied considerably: with risk prioritisation tending to correspond to the risks a respondent was most directly dealing with. Several key risk themes emerged, including: the Middle Class squeeze; Race, Transformation and Political Vulnerability; Competition and the Neo-Liberal Order; Innovation and Change vs Continuity; and Fragmentation, Identity, and Social Capital. Further research is needed to aid decisions by practitioners around the specific requirements of 21st century education, as well as to find solutions to re-shape the political economy of quality teacher supply.